Impact of E-Commerce Growth on Urban Logistics in France - Faure, Juliette (International Journal of Supply Chain and Logistics, 2024)
Purpose: The article aims to examine how e-commerce growth is affecting urban logistics, including traffic congestion, environmental impact, and warehouse demand. It explores challenges posed by increased last-mile deliveries and suggests ways cities can adapt for efficient, sustainable logistics. This analysis seeks to provide solutions for balancing consumer demand with urban sustainability. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The findings revealed that e-commerce growth intensifies urban congestion, increases emissions from delivery vehicles, and drives up demand for warehouse space near cities. These changes challenge urban infrastructure and logistics efficiency. Sustainable solutions, like green vehicles and optimized delivery networks, are essential to mitigate these impacts. Unique Contribution to Theory, Practice and Policy: Urban growth theory, resource-based view (RBV) & sustainable urban logistics theory may be used to anchor future studies on the impact of e-commerce growth on urban logistics. Practically, logistics companies and urban planners should implement region-specific solutions to manage the unique challenges of e-commerce growth. From a policy perspective, city governments should establish clear guidelines and incentives to encourage sustainable urban logistics practices.